Minimally Invasive Tissue Sampling Findings in 12 Patients With Coronavirus Disease 2019. (15th December 2021) - Rakislova, Natalia; Rodrigo-Calvo, Maria Teresa; Marimon, Lorena; Ribera-Cortada, Inmaculada; Ismail, Mamudo R; Carrilho, Carla; Fernandes, Fabiola; Ferrando, Melania; Sanfeliu, Esther; Castillo, Paola; Guerrero, José; Ramírez-Ruz, José; et al.
Abstract: Background: Minimally invasive tissue sampling (MITS), a postmortem procedure that uses core needle biopsy samples and does not require opening the body, may be a valid alternative to complete autopsy (CA) in highly infectious diseases such as coronavirus disease-19 (COVID-19). This study aimed to (1) compare the performance of MITS and CA in a series of COVID-19 deaths and (2) evaluate the safety of the procedure. Methods: From October 2020 to February 2021, MITS was conducted in 12 adults who tested positive before death for COVID-19, in a standard, well-ventilated autopsy room, where personnel used reinforced personal protective equipment. In 9 cases, a CA was performed after MITS. A thorough histological evaluation was conducted, and the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was evaluated by real-time reverse-transcription polymerase chain reaction (RT-PCR) and immunohistochemistry. Results: The diagnoses provided by MITS and CA matched almost perfectly. In 9 patients, COVID-19 was in the chain of events leading to death, being responsible for diffuse alveolar damage and mononuclear T-cell inflammatory response in the lungs. No specific COVID-19 features were identified. Three deaths were not related to COVID-19. All personnel involved in MITS repeatedly tested negative for COVID-19. SARS-CoV-2 was identified by RT-PCR and immunohistochemistry in the MITS samples, particularly in the lungs. Conclusions: MITS is useful for evaluating COVID-19–related deaths in settings where a CA is not feasible. The results of this simplified and safer technique are comparable to those of CA.